Is the normal shoulder rotation strength ratio altered in elite swimmers? - Boettcher, C.; Halaki, M.; Holt, K.; Ginn, K. A. (Medicine & Science in Sports & Exercise, 2020)
Introduction: It is commonly believed that the shoulder external rotation (ER) to internal rotation (IR) strength ratio is decreased in swimmers due to predominant IR loading during the pull-through (propulsive) phase which predisposes to shoulder pain. However, the evidence supporting this hypothesis is inconclusive. Therefore, the aim of this study was to examine shoulder rotation strength parameters in elite swimmers and investigate potential associations with shoulder pain. Methods: Sixty-eight (40 men; age, 19.9 ± 3.2 yr) elite swimmers provided demographic and shoulder pain history data before measurement of shoulder rotation strength. Mixed model analyses were used to examine differences in shoulder IR and ER strength normalized to body weight (BW) and the shoulder rotation strength ratio. A multinomial logistic regression model was utilized to examine associations between shoulder rotation strength parameters and shoulder pain. Results: Mean shoulder IR strength (BW) was approximately 0.29 for male swimmers and 0.26 for female swimmers. Mean shoulder ER strength (BW) was approximately 0.19 for male swimmers and 0.18 for female swimmer. The shoulder ER/IR strength ratio was approximately 0.70 bilaterally for all swimmers. There were no significant differences between dominant and nondominant shoulders in IR or ER strength normalized to BW (P = 0.547). There were no associations between any shoulder strength parameters and shoulder pain (r2 = 0.032, P = 0.107). Conclusions: Despite the high IR loading, optimal swimming technique does not alter the normal ER/IR strength ratio at the shoulder. Elite swimmers who report current or a history of shoulder pain demonstrate normal shoulder rotation strength ratios. The finding of symmetrical shoulder rotation strength points to side-to-side strength comparisons as a valuable clinical tool in managing swimmers with unilateral shoulder pain.